1987
DOI: 10.1111/j.1399-3054.1987.tb02865.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of endogenous gibberellin in seed and fruit development of tomato: Studies with a gibberellin‐deficient mutant

Abstract: The role of endogenous gibberellin (GA) in seed and fruit development was studied with the use of the GA‐deficient ga‐1 mutant of tomato (Lycopersicon esculentum Mill. cv. Moneymaker). Flowers of the ga‐1 mutant were abnormal and sterile, but parthenocarpic fruit development was observed occasionally on the dwarf plants. A single application of GA4+7 restored the fertility of the mutant flowers and resulted in seed set. Development of GA‐producing and GA‐deficient seeds in GA‐deficient fruits was compared by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
52
0
4

Year Published

1991
1991
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(62 citation statements)
references
References 15 publications
6
52
0
4
Order By: Relevance
“…A physiological role for GAs in Arabidopsis seed development also is in agreement with previous results suggesting that GAs are required for normal seed growth in the gib1 tomato mutant (Groot et al, 1987) and in GA-deficient mutants of barley (Chandler, 1999). Increased abortion of seeds carrying the 35S:2ox2 transgene also can explain the low transformation efficiency observed for this construct using vacuum infiltration, because this method initially generates transgenic seeds that must successfully complete development before transgenic plants can be identified (Ye et al, 1999).…”
Section: Gas and Seed Developmentsupporting
confidence: 79%
See 1 more Smart Citation
“…A physiological role for GAs in Arabidopsis seed development also is in agreement with previous results suggesting that GAs are required for normal seed growth in the gib1 tomato mutant (Groot et al, 1987) and in GA-deficient mutants of barley (Chandler, 1999). Increased abortion of seeds carrying the 35S:2ox2 transgene also can explain the low transformation efficiency observed for this construct using vacuum infiltration, because this method initially generates transgenic seeds that must successfully complete development before transgenic plants can be identified (Ye et al, 1999).…”
Section: Gas and Seed Developmentsupporting
confidence: 79%
“…In tomato, Groot et al (1987) used the GAdeficient gib1 mutant to suggest that GAs are required for normal seed growth. In pea, two alleles at the LH locus, lh-1 and lh-2 , have been used to demonstrate that GAs produced in the embryo and/or endosperm are required for normal seed growth and survival (Swain et al, 1993(Swain et al, , 1997.…”
Section: Introductionmentioning
confidence: 99%
“…These observations suggest that GAs are involved in the early stage of seed development in pea (Swain et al, 1995). On the other hand, Groot et al (1987) have reported that exogenous GA increased the seed weight and delayed seed dehydration of the GAdeficient ga-1 mutant of tomato (Lycopersicon esculentum), which suggests that GAs played a role even in the later stages of fruit and seed development in the tomato. Scialabba et al (1999) have observed starch grains in the integument of developing seeds of Brassica macrocarpa and their gradual degradation and disappearance during the process of seed maturation.…”
mentioning
confidence: 90%
“…Since GA, was not found as an endogenous GA in tomato, exogenous GA, could not have been as effective as endogenous GAs. Although tomato fruits may grow in the absence of endogenous GAs (ga-l mutant), they develop much better with GAs (Groot et al, 1987). Differences in GA-induced responses in tomato can be partially explained by timing of application (Sawhney, 1984).…”
Section: Fruit Development and Growth Regulatorsmentioning
confidence: 99%